2017
DOI: 10.1016/bs.ctdb.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cell Polarity by PAR-1/MARK Kinase

Abstract: PAR-1/MARK kinases are conserved serine/threonine kinases that are essential regulators of cell polarity. PAR-1/MARK kinases localize and function in opposition to the Anterior PAR proteins to control the asymmetric distribution of factors in a wide variety polarized cells. In this review, we discuss the mechanisms that control the localization and activity of PAR-1/MARK kinases, including their antagonistic interactions with the Anterior PAR proteins. We focus on the role PAR-1 plays in the asymmetric divisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 154 publications
(260 reference statements)
1
39
0
Order By: Relevance
“…Microtubule affinity-regulating kinases (MARKs) are an evolutionarily conserved family of kinases that comprise MARK1(PAR-1c), MARK2 (PAR-1b/EMK), MARK3 (PAR-1a/C-TAK1) and MARK4 (PAR-1d/MARKL1). 152 Mammalian MARKs are homologous to the invertebrate partitioning gene product Par-1, which regulates development of cell polarity, 153 and belong to the same family of energy sensing kinases as AMPK. 154 MARKs are indirectly associated with MTs, since they were identified as kinases that phosphorylate the MT-regulating proteins tau and MAPs, to regulate MT dynamics and MT-dependent transport.…”
Section: Mark Proteinsmentioning
confidence: 99%
“…Microtubule affinity-regulating kinases (MARKs) are an evolutionarily conserved family of kinases that comprise MARK1(PAR-1c), MARK2 (PAR-1b/EMK), MARK3 (PAR-1a/C-TAK1) and MARK4 (PAR-1d/MARKL1). 152 Mammalian MARKs are homologous to the invertebrate partitioning gene product Par-1, which regulates development of cell polarity, 153 and belong to the same family of energy sensing kinases as AMPK. 154 MARKs are indirectly associated with MTs, since they were identified as kinases that phosphorylate the MT-regulating proteins tau and MAPs, to regulate MT dynamics and MT-dependent transport.…”
Section: Mark Proteinsmentioning
confidence: 99%
“…Polarization kinetics are slower when one of those mechanisms is compromised. Further, although an anterior PAR domain can be established in the absence of PAR-2, PAR-2 is essential during the maintenance phase to prevent anterior PARs from invading the posterior domain (Rose and Gonczy, 2014;Wu and Griffin, 2017). Previous studies showed a weaker effect on polarity maintenance in par-1 mutants compared to par-2 mutants (Cuenca et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Several of the PAR polarity proteins are polarized along the anterior/posterior (AP) axis during polarity establishment. The PDZ-containing proteins PAR-3 and PAR-6 and the atypical protein kinase C, PKC-3, initially localize uniformly around the entire cell cortex, then become localized to the anterior domain, allowing PAR-2, a RING-finger protein, and PAR-1, a Ser/Thr kinase, localize to the reciprocal posterior domain of the embryo (Goldstein and Macara, 2007;Rose and Gonczy, 2014;Wu and Griffin, 2017). Following their establishment in these domains, PAR proteins mutually exclude each other from their distinct anterior and posterior domains to maintain cell polarity.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its powerful genetic tool kit and optically tractable eggs, C. elegans is one of the most thoroughly studied models for the assembly and migration of sperm asters. C. elegans eggs represent ã 50 µm oval-shaped cell type, consisting of the future anterior end containing the maternal meiotic spindle and the future posterior end where fertilization and entry of the male pronucleus occurs ( Figure 1A) [9]. The unfertilized egg is arrested in meiosis I, which resumes upon fertilization resulting in formation of the female pronucleus upon meiotic completion [10].…”
Section: Sperm Aster Growth and Centration In C Elegansmentioning
confidence: 99%